PERISTILAHAN DALAM RITUAL TUANG MINYAK PADA MASYARAKAT MELAYU SAMBAS: KAJIAN SEMANTIK - Atika, Nur; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â Abstract This study focuses on the terminology of oil pouring rituals in the Sambas Malay community, precisely in Semata Village, Tangaran District. Issues discussed in this study include inventory of terminology in oil pouring rituals, components of meaning, and semantic functions. This study aims to describe the terminology in the Malay oil pouring ritual in Sambas Regency. The method used in this research is descriptive linguistic method with a qualitative form. The source of the data in this study is the Sambas Malay language speech in the form of terminology in the pouring ritual of the Sambas Malay community spoken by several informants. The data in this study are terms about the tools, processes, time, actors, and place of implementation in the oil pouring ritual. The techniques used in this study were interviews and recording. Data collection tools used were interview instruments and voice recording devices. Based on the research conducted, there are 44 terms in the oil pouring ritual consisting of 24 tool terms, 10 process terms, 2 time terms, 6 actor terms, and 2 place terms. These terms as a whole have a lexical meaning and as many as 30 terms contain cultural meanings.Keywords: Terminology, Pouring Oil, Malay Sambas